2021
DOI: 10.3390/molecules26154700
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Celastrol in Central Nervous System Disorders: Highlights from In Vitro and In Vivo Approaches

Abstract: Celastrol, the most abundant compound derived from the root of Tripterygium wilfordii, largely used in traditional Chinese medicine, has shown preclinical and clinical efficacy for a broad range of disorders, acting via numerous mechanisms, including the induction of the expression of several neuroprotective factors, the inhibition of cellular apoptosis, and the decrease of reactive oxygen species (ROS). Given the crucial implication of these pathways in the pathogenesis of Central Nervous System disorders, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Study has reported that researchers used a multiple-hit rat model to explore the therapeutic effects of celastrol on infantile spasms. Considering the anti-inflammatory effects of celastrol and the important role of inflammation and immunity in epilepsy, their findings found that celatrol could have a therapeutic effect on the disease by inhibiting NF-kB ( Schiavone et al, 2021 ). Moreover, a study found that in a disease model of epilepsy, N-methyl- d -aspartate receptor-mediated activation of nicotinamide adenine dinucleotide phosphate oxidase (NOX) induces rapid release of H 2 O 2 , which is associated with epileptic seizures.…”
Section: Effects Of Triptolide and Celastrol On Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Study has reported that researchers used a multiple-hit rat model to explore the therapeutic effects of celastrol on infantile spasms. Considering the anti-inflammatory effects of celastrol and the important role of inflammation and immunity in epilepsy, their findings found that celatrol could have a therapeutic effect on the disease by inhibiting NF-kB ( Schiavone et al, 2021 ). Moreover, a study found that in a disease model of epilepsy, N-methyl- d -aspartate receptor-mediated activation of nicotinamide adenine dinucleotide phosphate oxidase (NOX) induces rapid release of H 2 O 2 , which is associated with epileptic seizures.…”
Section: Effects Of Triptolide and Celastrol On Epilepsymentioning
confidence: 99%
“…Celastrol is derived from a wide variety of natural plants and accounts for a large percentage of the extracts of the roots of TWHF ( Lange et al, 2017 ). Studies have found that triptolide and celastrol are therapeutically effective in preclinical and clinical studies in a variety of diseases, which may be related to their anti-inflammatory and antioxidant effects ( Gao et al, 2021 ; Schiavone et al, 2021 ). Because of their small molecular weight and lipophilicity, they can cross the blood-brain barrier and work in the brain, so they have been studied in many neurological diseases ( Cleren et al, 2005 ; Lu et al, 2010 ; De Angelis et al, 2020 ), and their roles in neurological diseases are the focus of this review ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The potential mechanism of celastrol in neuroprotective effect deserves further investigation. Celastrol is the most abundant compound extracted from the root of Tripterygium wilfordii ( Salminen et al, 2010 ), which has exhibited preclinical and clinical efficacy in a broad range of diseases such as cancer, rheumatoid arthritis ( Tao et al, 1989 ), ulcerative colitis ( Gao et al, 2020 ), and central nervous system disease ( Schiavone et al, 2021 ) due to its different pharmacological properties. Celastrol was demonstrated to exert anticancer effects in many types of tumors such as breast cancer ( Yang et al, 2011 ), retinoblastoma ( Li Z. et al, 2012 ), gastric cancer ( Sha et al, 2015 ), and melanoma ( Abbas et al, 2007 ) by suppressing tumor migration, invasion and angiogenesis as well as promoting autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of celastrol as a neuroprotective agent in the above NDDs was not fully elucidated. However, preclinical studies suggested that it exerts its neuroprotective effects through multiple mechanisms, mainly through its anti-inflammatory and antioxidant actions [ 115 ]. This is supported by the fact that it can suppress many steps in the initial stages of inflammation and OS, including signaling pathways for HSP90 and NF-κB, a transcription factor thought to play an important role in gene regulation during OS and inflammation.…”
Section: Celastrolmentioning
confidence: 99%